Assessment of liquefaction hazard along shoreline areas of Peninsular Malaysia. Issue 2 (15th December 2017) - Hashim, Huzaifa; Suhatril, Meldi; Hashim, Roslan
ABSTRACT: Using a collection of 2074 boreholes extracted from soil investigation reports utilized by standard penetration test, this study examines the susceptibility of soil liquefaction hazard along the shoreline of Peninsular Malaysia. Data collection and site visit were conducted to gather all the basic information related to soil liquefaction hazard. Three types of results are presented in the form of photos (recent shoreline condition), graphical illustrations (soil composition, SPT-N distribution and zone of saturation) and liquefaction susceptibility plots. The findings indicate there is obviously a critical need to adapt further liquefaction analysis in the shoreline region of Peninsular Malaysia to better understand liquefaction hazard and produced beneficial information on the matter. A risk assessment matrix is also introduced in classifying the severity and recommended mitigation measures of the studied areas.